Kunst Markt Köln 1969. - Art Cologne, Köln (Köln : Kunstmarkt Köln, 1969)
Abularach, Rodolfo ; Aeschbacher, Hans ; Albers, Josef ; Alechinsky, Pierre ; Alt, Otmar ; Altenbourg, Gerhard ; Alviani, Getulio ; Andre, Carl ; Antes, Horst ; Anuszkiewicz, Richard ; Arakawa, Shusaku ; Arman ; Arp, Hans (Jean) ; Avedisian, Edward ; Avramidis, Joannis ; Baer, Jo ; Bannard, Darby ; Baruchello, Gianfranco ; Baumeister, Willi ; Bechthold, Erwin ; Bellmer, Hans ; Berrocal, Miguel ; Beuys, Joseph ; Bissier, Julius ; Bochner, Mel ; Böhm, Hartmut ; Böhmler, Claus ; Bonato, Victor ; Bonomi, Maria ; Bontecou, Lee ; Botero, Fernando ; Brehmer, Klaus-Peter ; Brouwn, Stanley ; Brüning, Peter ; Bubenik, Gernot ; Bury, Pol ; Buscioni, Umberto ; Buthe, Michael ; Calderara, Antonio ; de Camargo, Sergio ; Campigli, Massimo ; Castro, Lourdes ; Chaissac, Gaston ; Chillida, Eduardo ; Christensen, Dan ; Christo ; Chryssa ; Cimiotti, Emil ; Copley, William ; Corneille ; Cote, Alan ; Cruz-Diez, Carlos ; Dado ; Danby, Ken ; Darboven, Hanne ; Dichgans, Christa ; Diehl, Hans Jürgen ; Dietrich, HJ ; Dine, Jim ; Distel, Herbert ; Dix, Otto ; Dizi ; Dohr, Günter ; Dorazio, Piero ; Dreyer, Paul Uwe ; Duarte, Angel ; Dubuffet, Jean ; Ernst, Christo Jimmy ; Ernst, Max ; Feininger, Lyonel ; Riverhead (New York) ; Fontana, Lucio ; Francis, Sam ; Freimann, Christoph ; Fruhtrunk, Günter ; Gallo, Frank ; Geiger, Rupprecht ; Geipel, Hans ; Geissler, Paul-Julius ; Geldmacher, Klaus ; Gerolds ; Gerresheim, Bert ; Gerstner, Karl ; Girke, Raimund ; Glasmeier, Rolf ; Goepfert, Hermann ; Goller, Bruno ; Gonschior, Kuno ; Goode, Joe ; Gosewitz, Ludwig ; Götzinger, Herbert ; Graeser, Camille ; Graham, Robert ; Gräsel, Friedrich ; Graubner, Gotthard ; Grosse, Hannes ; Haack, Dieter ; Hacklin, Allan ; Häfner, Thomas ; Hamilton, Richard ; Hartung, Hans ; Hauser, Erich ; etc.
Kunstmarkt Köln 1969, Kunsthalle und des Kunstvereins der Stadt Köln, 14. Oktober - 9. November 1969
kunstcatalogus